Exploring teachers’ perceptions and practices of integrating critical thinking skills in teaching reading - Amale, Michael; Gebretsadik, Abebe ((JELE) Journal Of English Language and Education, 2023)
This study was aimed to explore the teachers’ perceptions and practices of infusing critical thinking skills into reading instruction to improve students’ reading comprehension. It also identified the perceived challenges that hinder the practices of critical thinking skills in reading classes. The research utilized a descriptive survey design and an explanatory mixed-methods approach to collect data. The study involved 40 out of 52 English instructors and three reading texts teachers used to practice reading comprehension questions were randomly selected. Besides, texts used for quiz, mid-exam and final examination were purposely collected to evaluate the text to which the teachers integrated critical thinking skills classroom reading activities and assessments. Quantitative data was gathered through questionnaires, while qualitative data was obtained through document analysis. Statistical analysis was conducted using SPSS version 24, and content analysis was used for the qualitative data. The survey results revealed that teachers had moderate level of perceptions of integrating critical thinking skills (m=3.59) and identified that student-related challenges (m= 3.76) as significant obstacles to practice critical thinking skills. The results of document analysis indicated that critical thinking skills practiced rarely. It can be concluded that teachers' conceptual perception at moderate level was not adequate to infuse critical thinking skills into reading instruction to enhance students' reading comprehension. Therefore, it is crucial to train teachers in the integration of critical thinking skills into an interactive reading curriculum to motivate and engage students and help them understand the reading skills more deeply. Further research is recommended to explore the impact of teachers' perceptions of critical thinking skills on students' reading comprehension